Argumentieren lernen Aufgaben für den Philosophie- und Ethikunterricht - Franzen, Henning (Wissenschaftliche Buchgesellschaft (wbg), 2023)
The development of argumentative skills is a central goal of ethics and philosophy lessons, indeed a central educational goal in general. But how can that succeed? The present collection of tasks offers teachers rich materials for the spiral curricular, systematic promotion of argumentative skills based on exemplary content. Based on clear professional standards, there are tasks at four levels, each in connection with clear information sheets. The tasks of the two lower levels can already be used for younger learners of the secondary levels, tasks of the highest level are aimed at learners of the final classes or the introductory phase. For the teachers, the tasks and leaflets are supplemented by technical and didactic comments as well as solution tips.